Oral Dysbiotic Communities and Their Implications in Systemic Diseases - Preethi Sudhakara; Abishek Gupta; Anshumouli Bhardwaj; Aruni Wilson (MDPI AG, 2018)
The human body supports the growth of a wide array of microbial communities in various niches such as the oral cavity, gastro-intestinal and urogenital tracts, and on the surface of the skin. These host associated microbial communities include yet-un-cultivable bacteria and are influenced by various factors. Together, these communities of bacteria are referred to as the human microbiome. Human oral microbiome consists of both symbionts and pathobionts. Deviation from symbiosis among the bacterial community leads to “dysbiosis”, a state of community disturbance. Dysbiosis occurs due to many confounding factors that predispose a shift in the composition and relative abundance of microbial communities. Dysbiotic communities have been a major cause for many microbiome related systemic infections. Such dysbiosis is directed by certain important pathogens called the “keystone pathogens”, which can modulate community microbiome variations. One such persistent infection is oral infection, mainly periodontitis, where a wide array of causal organisms have been implied to systemic infections such as cardio vascular disease, diabetes mellitus, rheumatoid arthritis, and Alzheimer’s disease. The keystone pathogens co-occur with many yet-cultivable bacteria and their interactions lead to dysbiosis. This has been the focus of recent research. While immune evasion is one of the major modes that leads to dysbiosis, new processes and new virulence factors of bacteria have been shown to be involved in this important process that determines a disease or health state. This review focuses on such dysbiotic communities, their interactions, and their virulence factors that predispose the host to other systemic implications.